Association between Polymorphisms of Alpha-Adducin Gene and Essential Hypertension in Chinese Population. (20th December 2012) - Zhang, Li-na; Ji, Lin-dan; Fei, Li-juan; Yuan, Fang; Zhang, Yue-miao; Xu, Jin
Abstract : The association between polymorphisms of α -adducin ( ADD1 ) gene and essential hypertension is still unclear. Thus, we carried out a case-control study and an interaction analysis to test whether ADD1 is a common candidate gene for hypertension in the Chinese population. Blood samples and information including body mass index (BMI), smoking habit, and alcohol abuse were collected. Meanwhile, total cholesterol, high density lipoprotein, triglyceride were measured by automatic biochemistry analyzer. All 6 tag single nucleotide polymorphisms (tagSNPs) within ADD1 gene were genotyped by SNPstream genotyping system. Multifactor dimensionality reduction (MDR) was used to identify the interactions among the SNPs and the non-genetic factors. Results showed that plasma triglyceride, total cholesterol, and BMI were significantly higher in the hypertensive group than in the control group. Result from genotyping indicated that rs4963 was significantly associated with essential hypertension. After stratification by gender, rs4963 was associated with essential hypertension only in males. MDR analysis indicated that interaction among BMI, rs4963, and rs16843452 were involved in susceptibility of hypertension. The present study indicated that rs4963 within ADD1 gene was associated with essential hypertension in Chinese population, which might be related to altered exonic splicing and disrupted gene regulation.